2020
DOI: 10.1177/1533033820905832
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Ultrasound in Medullary Thyroid Carcinoma: A Comparison With Computed Tomography

Abstract: Purpose: To explore the clinical value of ultrasound in the diagnosis of medullary thyroid carcinoma by comparing with enhanced computed tomography. Methods: This retrospective study was performed on 62 patients with pathologically confirmed medullary thyroid carcinoma. All patients underwent ultrasound and enhanced computed tomography examinations before surgery. The findings of the pathologic examination of resected specimens were considered as gold standard and were compared with the results of these 2 meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
0
12
0
4
Order By: Relevance
“…Ultrasound (US) is first-line imaging for patients with suspected MTC and is associated with 75.3% sensitivity, 93.1% specificity, and overall accuracy 80.4%. 29 US features associated with MTC include irregular shape, height/width ratio <1, lack of a peripheral halo, hypoechogenecity, calcification (typically macrocalcification), and hypervascularity. 29 31 Two studies that compared US features of papillary thyroid cancer (PTC) versus MTC both found larger lesion size, heterogeneous echotexture, and hypervascularity as significantly more characteristic of MTC than PTC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound (US) is first-line imaging for patients with suspected MTC and is associated with 75.3% sensitivity, 93.1% specificity, and overall accuracy 80.4%. 29 US features associated with MTC include irregular shape, height/width ratio <1, lack of a peripheral halo, hypoechogenecity, calcification (typically macrocalcification), and hypervascularity. 29 31 Two studies that compared US features of papillary thyroid cancer (PTC) versus MTC both found larger lesion size, heterogeneous echotexture, and hypervascularity as significantly more characteristic of MTC than PTC.…”
Section: Resultsmentioning
confidence: 99%
“…US is superior to axial or functional imaging for detecting initial intrathyroidal tumor and initial or recurrent neck lymph node metastases. 29 , 34 …”
Section: Resultsmentioning
confidence: 99%
“…La mayor parte de los autores coinciden en que el CMT comparte algunas características con el CPT como la hipoecogenicidad, la ausencia de halo y la presencia de calcificaciones y de adenopatías [23][24][25][26][27]. Sin embargo, algunos estudios que han comparado las características ecográficas de ambos tumores han encontrado que el CMT generalmente presenta un tamaño superior y mayor frecuencia de cambios quísticos, de márgenes bien definidos y de morfología ovalada, siendo por el contrario la forma más alta que ancha más típica del CPT [24][25][26][27][28][29][30][31][32][33][34][35]. Por tanto, parece que en la ecografía del CMT las características sospechosas de malignidad podrían ser menos frecuentes que en el CPT, y en ese caso un porcentaje no despreciable de casos se consideraría como ecográficamente no sospechoso [34][35][36][37].…”
Section: Anticuerpos Heterófilos Macrocalcitoninaunclassified
“…MTC on imaging is mostly hypoechoic, has macro- and microcalcifications, is patchy in structure and is vascularized, mainly perinodular. There is rarely a peripheral halo effect [ 15 , 43 ]. It is useful to combine US methods with the measurement of serum Ctn and CEA, which significantly increases the sensitivity of the diagnosis (US vs.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional CT is used mainly in the search for MTC metastases in the lungs, mediastinal lymph nodes and liver [ 25 , 46 ]. CT does not play a major role in the diagnosis of primary tumors, showing both lower sensitivity (61.6% vs. 75.3%) and specificity (82.8% vs. 93.1%) than the US in the hands of an experienced diagnostician [ 43 ].…”
Section: Introductionmentioning
confidence: 99%